THE EFFECT OF AUDIT QUALITY, PROFITABILITY, AND AUDIT COMMITTEE CHARACTERISTICS ON EARNINGS MANAGEMENT (An Empirical Study on Transportation and Logistics Sector Companies Listed on the Indonesia Stock Exchange for the 2019–2023 Period) - Made Gayatri Marchia; Ni Nyoman Sri Rahayu Trisna Dewi (Adisam Publisher, 2025)
This study aims to examine the effect of audit quality, profitability, audit committee size, and audit committee expertise in accounting and finance on earnings management in transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Earnings management is measured using discretionary accruals based on the Modified Jones Model. Audit quality is proxied by affiliation with Big Four public accounting firms, profitability is measured using Return on Assets (ROA), audit committee size is measured by the number of members, and audit committee expertise is assessed by the proportion of members with backgrounds in accounting and finance. This research employs a quantitative method with an associative approach. The sample consists of 158 firm-year observations selected through purposive sampling. Data were obtained from annual reports available on the official IDX website and company websites, and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression analysis. Hypothesis testing was conducted using F-tests and t-tests to determine the simultaneous and partial effects of each independent variable on earnings management. The results indicate that audit quality, profitability, and audit committee size have no significant effect on earnings management. However, audit committee expertise in accounting and finance has a significant negative effect on earnings management. These findings highlight the importance of professional competence within the audit committee in enhancing financial oversight and preventing earnings manipulation.